(untitled) (Direito e Humanidades, 2010)
From a corner of international law hails a discipline which has historically caused mischief: international investment law. The last few decades have witnessed an interesting development: the channeling of disputes stemming there from through a private dispute resolution mechanism: arbitration. Albeit successful in other realms, its luck in Latin American is still an open question. And as history would have it, the (incipient) Latin American flavor is becoming a matter of concern. This paper comments on it, providing insight as to the right course of action and the implications of failing to follow it. Keywords: arbitration, international law, investment disputes.